A Novel Online Detection System for Wheelset Size in Railway Transportation. (31st July 2016) - Cheng, Xiaoqing; Chen, Yuejian; Xing, Zongyi; Li, Yifan; Qin, Yong
Abstract : The online detection of wheelset size has important implications for ensuring the safety of railway operation and decreasing the maintenance costs. Based on laser displacement sensors (LDS), a novel online detection system of the wheel size is proposed using only six two-dimensional LDS and two one-dimensional LDS. The calculation principles of tread profile and wheel diameter are given, as well as the calibration method. Errors induced by wheel-rail vibration, misalignment, sensor noise, S-shape running, and wheelset differential are also analyzed. After system implementation, field experiments were performed using both standard wheel and several real trains. It turns out that the detection uncertainty of flange width and height is 0.1 mm and wheel diameter 0.3 mm, which can meet the requirements of maintenance.